Working Memory Capacity Limits Motor Learning When Implementing Multiple Instructions - Buszard, Tim; Farrow, Damian; Verswijveren, Simone J. J. M.; Reid, Machar; Williams, Jacqueline; Polman, Remco; Ling, Fiona Chun Man; Masters, Rich S. W. (Frontiers in Psychology, 2017)
Although it is generally accepted that certain practice conditions can place large demands on working memory (WM) when performing and learning a motor skill, the influence that WM capacity has on the acquisition of motor skills remains unsubstantiated. This study examined the role of WM capacity in a motor skill practice context that promoted WM involvement through the provision of explicit instructions. A cohort of 90 children aged 8 to 10 years were assessed on measures of WM capacity and attention. Children who scored in the lowest and highest thirds on the WM tasks were allocated to lower WM capacity (n = 24) and higher WM capacity (n = 24) groups, respectively. The motor task required children to practice basketball shooting for 240 trials in blocks of 20 shots, with pre- and post-tests occurring before and after the intervention. A retention test was also administered one week after the post-test. Prior to every practice block, children were provided with five explicit instructions that were specific to the step-by-step processes of shooting a basketball. Results revealed that the higher WM capacity group displayed consistent improvements from pre- to post-test and through to the retention test, while the opposite effect occurred in the lower WM capacity group. This implies that the explicit instructions had a negative influence on learning by the lower WM capacity children. The results are discussed in relation to strategy selection for dealing with instructions and the role of attention control.